2018
DOI: 10.3350/cmh.2017.0059
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of glomerular filtration rates and neutrophil gelatinase-associated lipocalin during treatment with direct acting antivirals

Abstract: Background/AimsCorrect renal function evaluation is based on estimated glomerular filtration rates (eGFR) and complementary renal damage biomarkers, such as neutrophil gelatinase associated lipocalin (NGAL). The aim of this study was to evaluate eGFR and NGAL modifications and renal impairment during treatment with a direct acting antiviral (DAA) for chronic hepatitis C virus (HCV) infection.MethodsA retrospective cohort study evaluated eGFR modification during treatment with DAA. Subgroup analysis on serum NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…All these characteristics (advanced age, comorbidities, and high burden of comedications) could potentially affect tolerability of HCV treatment and adherence in this subgroup [7]. Moreover, some possible side effects and biomarker alterations, as well as increased risk of liver cancer, have been reported by several authors, especially in elderly people [8][9][10][11][12][13]. In addition, the presence of some side effects was in particular reported among those who had concurrent comorbidities (such as liver cirrhosis, cardiac failure, and advanced age) [14,15].…”
Section: Introductionmentioning
confidence: 96%
“…All these characteristics (advanced age, comorbidities, and high burden of comedications) could potentially affect tolerability of HCV treatment and adherence in this subgroup [7]. Moreover, some possible side effects and biomarker alterations, as well as increased risk of liver cancer, have been reported by several authors, especially in elderly people [8][9][10][11][12][13]. In addition, the presence of some side effects was in particular reported among those who had concurrent comorbidities (such as liver cirrhosis, cardiac failure, and advanced age) [14,15].…”
Section: Introductionmentioning
confidence: 96%
“…It has been suggested that DAA therapy may have transient negative impacts on renal function. 33,34 We observed that the renal function was not affected at 3 months after the end of treatment, compared to the pretreatment levels, thus indicating that the modification of SUA was not affected by the change in renal function in this study.…”
Section: Discussionmentioning
confidence: 50%
“…e recent availability of direct-acting antivirals (DAAs) has led to a revolution in the treatment of HCV infections, being a highly effective treatment option irrespective of the stage of liver fibrosis [15]. However, there have been concerns about renal function deterioration associated with DAAs [5].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study conducted by Strazzulla et al attempted to retrospectively investigate the role of NGAL in evaluating the effect of sofosbuvir-based antivirals on renal tubules, in 18 patients with chronic HCV infection. No large prospective studies have been published about this issue [5]. Hence, this study aimed to assess serum NGAL both before and after the twelve weeks of therapy with sofosbuvir-based regimen, in a larger population of HCV RNA-positive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation